Tourism and visual culture. - Burns, Peter (Peter M.); Lester, Jo-Anne; Bibbings, Lyn (CAB International, 2010)
Explores the significance of tourism as a significant phenomenon in both generating and receiving societies, examining methods and cases that demonstrate, develop, and affirm tourism's essentially visual nature. This work uses tourism-related methodology such as photographs, souvenirs and advertising material to discuss findings.